Using trigger tools to identify triage errors by ambulance dispatch nurses in Sweden: an observational study - Ulrika Winblad; Douglas Spangler; Lennart Edmark; Jessica Colldén-Benneck; Helena Borg; Hans Blomberg (BMJ Open)
Objectives This study aimed to assess whether trigger tools were useful identifying triage errors among patients referred to non-emergency care by emergency medical dispatch nurses, and to describe the characteristics of these patients.Design An observational study of patients referred by dispatch nurses to non-emergency care.Setting Dispatch centres in two Swedish regions.Participants A total of 1089 adult patients directed to non-emergency care by dispatch nurses between October 2016 and February 2017. 53% were female and the median age was 61 years.Primary and secondary outcome measures The primary outcome was a visit to an emergency department within 7 days of contact with the dispatch centre. Secondary outcomes were (1) visits related to the primary contact with the dispatch centre, (2) provision of care above the primary level (ie, interventions not available at a typical local primary care centre) and (3) admission to hospital in-patient care.Results Of 1089 included patients, 260 (24%) visited an emergency department within 7 days. Of these, 209 (80%) were related to the dispatch centre contact, 143 (55%) received interventions above the primary care level and 99 (38%) were admitted to in-patient care. Elderly (65+) patients (OR 1.45, 95% CI 1.05 to 1.98) and patients referred onwards to other healthcare providers (OR 1.58, 95% CI 1.15 to 2.19) had higher likelihoods of visiting an emergency department. Six avoidable patient harms were identified, none of which were captured by existing incident reporting systems, and all of which would have received an ambulance if the decision support system had been strictly adhered to.Conclusion The use of these patient outcomes in the framework of a Global Trigger Tool-based review can identify patient harms missed by incident reporting systems in the context of emergency medical dispatching. Increased compliance with the decision support system has the potential to improve patient safety.